Empirical inspection of broadband growth nexus: A fixed effect with driscoll and Kraay standard errors approach - Bilal Mehmood; Hassan Mustafa (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Broadband has become an integral part of digital infrastructure of countries around the globe even in developing regions. Accordingly, this paper investigates the broadband growth nexus for 24 Asian countries for period 2001-2011. Using fixed effects with Driscoll and Kraay standard errors, the effect of broadband on economic growth is found positive. Recommendations include the policy step to bring the skills of human capital in these countries at par with developed countries that have benefitted substantially from broadband technology.
Keywords: 330; broadband; economic growth; fixed effects estimation; digital infrastructure; Asian region